2023
DOI: 10.1109/jestpe.2023.3270375
|View full text |Cite
|
Sign up to set email alerts
|

A 99.74% Efficient Capacitor-Charging Converter Using Partial Power Processing for Electrocalorics

Abstract: This work combines a 99.2% efficient GaN-based low-voltage fast-switching half-bridge converter with a Si-based high-voltage slow-switching and almost lossless switched capacitor multiplexer using a partial power processing approach to a six-level prototype with 99.74% efficiency. A loss breakdown shows how the ideal partial power processing efficiency is theoretically increased to 99.84% by using four additional voltage levels, but then reduced to the measured efficiency by the additional static and dynamic l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 59 publications
0
7
0
Order By: Relevance
“…Concomitantly, low hysterestic losses, U loss , and thus low remanent polarization, P r , are maintained in the 0.2% DB-modified polymers, because the increase of the alltrans containing crystalline phase, φ FE , remains limited. Both of these trends (summarized schematically in Figure 2c) contribute to the increase of ΔT EC , which is proportional to the electricfield-induced polarization change P P r max 2 2 . 20 Broadband dielectric spectroscopy (BDS) was used to further quantify the effect of the introduction of DB on the structure of P(VDF-ter-TrFE-ter-CFE) and elucidate the origin of the dielectric enhancement.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Concomitantly, low hysterestic losses, U loss , and thus low remanent polarization, P r , are maintained in the 0.2% DB-modified polymers, because the increase of the alltrans containing crystalline phase, φ FE , remains limited. Both of these trends (summarized schematically in Figure 2c) contribute to the increase of ΔT EC , which is proportional to the electricfield-induced polarization change P P r max 2 2 . 20 Broadband dielectric spectroscopy (BDS) was used to further quantify the effect of the introduction of DB on the structure of P(VDF-ter-TrFE-ter-CFE) and elucidate the origin of the dielectric enhancement.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Lowefficiency and high global warming impact technologies must be phased-out from the RC. With theoretical efficiency over 80%, 1,2 solid-state cooling based on the electrocaloric (EC) effect has emerged as a serious candidate to facilitate this transition, but its potential for applications is still hindered by the low performance of EC materials. EC cooling is based on the electrocaloric effect (ECE), which arises from the increase of the net polarization in polar crystals upon the application of an external electric field, E. Under adiabatic conditions, the system compensates the decrease of dipolar entropy (inherent to the alignment of dipoles) with an increase in lattice vibration entropy, i.e., an adiabatic temperature increase, ΔT EC , thus keeping the overall entropy of the system constant.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Compared with the base TP (COP mat is 10.9), the DMHD-modified TPD-1% exhibited excellent refrigeration efficiency of 91% (COP mat is 27.4), considering a 100% charge recovery ratio (Fig. 4G), which has been achieved in a custom-made charge recovery circuit for EC technology ( 55 ). By operating under an ultralow electric field, the TPD-1% offered a greatly improved COP mat that could further reduce the size and weight of the power source for a potential portable EC cooling device.…”
Section: Dielectric Analysis and Long-term Operationmentioning
confidence: 99%
“…Therefore, these results show that energy recovery is key to improve the efficiency of electrocaloric systems. Very recently, Mönch et al showed that an energy recovery as high as 99.7% is possible, which is very promising (41).…”
Section: High Efficiencymentioning
confidence: 99%
“…Very recently, Mönch et al . showed that an energy recovery as high as 99.7% is possible, which is very promising ( 41 ).…”
Section: High Efficiencymentioning
confidence: 99%